Discovering practical theology : exploring boundaries - Dillen, Annemie; Gärtner, Stefan, 1965- (Louvain theological & pastoral monographs, 2020)
Religion takes different shapes in late-modern society. Pastoral care, church and religion are also in transition. Practical theology explores these new challenges. This book introduces the readers to the field of this discipline in dialogue with the metaphor of 'boundaries'. Theoretical insights in practical theology and its methodology are combined with discussions about specific topics and case studies from the field of pastoral and spiritual care, with special attention for Catholic contexts. Practical theologians are presented as cross-border workers, whose work is to reflect on ambiguous places and borderlands 'in between' positions, disciplines, and fixed identities. Specific attention goes to questions on hope and power in relation to pastoral care, on chaplaincy in prisons and hospitals, on children and theology. This book functions also as an introduction to empirical methodologies and hermeneutical theological reflections. Transl. of the Dutch publication 'Praktische theologie. Verkenningen aan de grens' (Lannoo, 2015).